Covered Interest Parity Deviations : Macrofinancial Determinants - Cerutti, Eugenio (IMF Working Papers; Working Paper ;, 2019)
For about three decades until the Global Financial Crisis (GFC), Covered Interest Parity (CIP) appeared to hold quite closely-even as a broad macroeconomic relationship applying to daily or weekly data. Not only have CIP deviations significantly increased since the GFC, but potential macrofinancial drivers of the variation in CIP deviations have also become significant. The variation in CIP deviations seems to be associated with multiple factors, not only regulatory changes. Most of these do not display a uniform importance across currency pairs and time, and some are associated with possible temporary considerations (such as asynchronous monetary policy cycles).